Spectrum Sharing in Cognitive Radio Using GSC with Suppressed Sidelobes. (4th June 2014) - Hussain, Syed Azmat; Malik, Aqdas Naveed; Khan, Zafar Ullah; Qureshi, Ijaz Mansoor
Cognitive radio system is an innovative technology in the wireless communication that has the capability to smartly communicate with each other by opportunistically exploiting the vacant spectrum of primary users. In this work we present a new idea of sidelobe suppression applicable for cognitive users on transmitter and receiver sides. In case of spectrum sharing with the primary users by suppressing the side-lobes at the transmitter and receiver side, the cognitive users will be able to increase the throughput without cooperating the permissible interference temperature limit of the license spectrum. We suggest two generalized sidelobe cancellers (GSCs) that operate in parallel. The first GSC planned to attain the two conflicting objective at the same moment: firstly maximize the cognitive users self throughput; secondly minimize the interference generated by cognitive users at each primary receiver. The second GSC generates two main beams at the positions of the highest amplitude sidelobes of the first one. The values of main beams are equal to the two sidelobe peaks. The subtraction of the outputs of the two GSCs, results in the suppression of the highest pair of sidelobes. This process is repeated iteratively to result in an adaptive algorithm. Simulation results are there to provide the effectiveness of the proposed algorithm.